2022
DOI: 10.3389/fpls.2022.869583
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Phylogenomic Incongruence Underlies Evolutionary Relationships in Eyebrights (Euphrasia, Orobanchaceae)

Abstract: Disentangling the phylogenetic relationships of taxonomically complex plant groups is often mired by challenges associated with recent speciation, hybridization, complex mating systems, and polyploidy. Here, we perform a phylogenomic analysis of eyebrights (Euphrasia), a group renowned for taxonomic complexity, with the aim of documenting the extent of phylogenetic discordance at both deep and at shallow phylogenetic scales. We generate whole-genome sequencing data and integrate this with prior genomic data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…This pattern of recolonisation from multiple refugia is common in many European plant groups and leaves a distinct genetic signature (Huck et al, 2009; Petit et al, 2002; Valtueña et al, 2012). In Euphrasia , previous phylogenetic studies using widespread European sampling showed that there were multiple waves of colonisation to Britain (Garrett et al, 2022; Gussarova et al, 2008), while studies of phylogeography in the Euphrasia minima complex found persistence in multiple refugia: one from North America where plants subsequently colonised Greenland/Iceland/Norway, and the other from the Russian Ural mountains where populations subsequently spread to Svalbard (Gussarova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern of recolonisation from multiple refugia is common in many European plant groups and leaves a distinct genetic signature (Huck et al, 2009; Petit et al, 2002; Valtueña et al, 2012). In Euphrasia , previous phylogenetic studies using widespread European sampling showed that there were multiple waves of colonisation to Britain (Garrett et al, 2022; Gussarova et al, 2008), while studies of phylogeography in the Euphrasia minima complex found persistence in multiple refugia: one from North America where plants subsequently colonised Greenland/Iceland/Norway, and the other from the Russian Ural mountains where populations subsequently spread to Svalbard (Gussarova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Species readily hybridise, with 71 hybrid combinations identified to date, based on morphology (Metherell & Fred, 2018). Phylogenomic analyses have revealed extremely close relationships between species, with British samples showing 99.8% pairwise sequence identity based on complete plastid genomes (Garrett et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high degree of tetraploid subgenome divergence (~5%; Becher et al, 2020 ) has benefits for genomic analyses, increasing confidence in the assignment of short reads to the appropriate subgenome. British tetraploids are thought to have a common origin in mainland Europe and to have subsequently colonized the British Isles (Garrett et al, 2022 ).…”
mentioning
confidence: 99%